A pilot to assess target engagement of terazosin in Parkinson's disease. (January 2022) - Schultz, Jordan L.; Brinker, Alivia N.; Xu, Jia; Ernst, Sarah E.; Tayyari, Fariba; Rauckhorst, Adam J.; Liu, Lei; Uc, Ergun Y.; Taylor, Eric B.; Simmering, Jacob E.; Magnotta, Vincent A.; Welsh, Michael J.; et al.
Abstract: Background: Impaired brain energy metabolism is a key feature of Parkinson's disease (PD). Terazosin (TZ) binds phosphoglycerate kinase 1 and stimulates its activity, which enhances glycolysis and increases ATP levels. Preclinical and epidemiologic data suggest that TZ may be neuroprotective in PD. We aimed to assess target engagement and safety of TZ in people with PD. Methods: We performed a 12-week pilot study in people with PD. Participants were randomized to receive 5 mg TZ or placebo. Participants and study personnel were blinded. We assessed TZ target engagement by measuring brain ATP with 31 P-magnetic resonance spectroscopy (MRS) and whole blood ATP with a luminescence assay. Robust linear regression models compared changes between groups controlling for baseline brain and blood ATP levels, respectively. We also assessed clinical measures of PD and adverse events. Results: Thirteen participants were randomized. Mild dizziness/lightheadedness was more common in the TZ group, and three participants taking TZ dropped out because of dizziness and/or orthostatic hypotension. Compared to the placebo group, the TZ group had a significant increase in the ratio of βATP to inorganic phosphate in the brain. The TZ group also had a significant increase in blood ATP levels compared to the placebo group (p < 0.01). Conclusions: This pilot study suggests that TZ may engage its target and change ATP levels in the brain and blood of people with PD. Further studies may be warranted to test the disease-modifying potential of TZ. Highlights: In people with Parkinson's disease, terazosin increased brain ATP levels as measured by 31 P magnetic resonance spectroscopy. Terazosin increased ATP levels in blood. Terazosin may engage its target, phosphoglycerate kinase 1, in Parkinson's disease. Terazosin use in Parkinson's disease may require vigilance for orthostatic symptoms.